Jinggangmycin-Induced UDP-Glycosyltransferase 1-2-Like Is a Positive Modulator of Fecundity and Population Growth in Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) - Ge, Lin Quan; Zheng, Sui; Gu, Hao Tian; Zhou, Yong Kai; Zhou, Ze; Song, Qi Sheng; Stanley, David (Frontiers in Physiology, 2019)
The antibiotic jinggangmycin (JGM) is broadly applied in Chinese rice producing regions to control rice blight, a fungal disease. Aside from protecting rice plants from the disease, JGM leads to the unexpected action of stimulating brown planthopper (BPH; Nilaparvata lugens; Hemiptera: Delphacidae) reproduction to the extent it can influence population sizes. The JGM-induced BPH population growth has potential for severe agricultural problems and we are working to understand and mitigate the mechanisms of the enhanced reproduction. UDP-glucuronosyltransferases (UGTs) are multifunctional detoxification enzymes responsible for biotransformation of diverse lipophilic compounds. The biological significance of this enzyme family in insect fecundity is not fully understood, however, upregulated UGT12 in JGM-treated BPH, may influence fecundity through metabolism of developmental hormones. This idea prompted our hypothesis that NlUGT12 is a positive modulator of BPH reproductive biology. JGM treatment led to significant increases in accumulations of mRNA encoding NlUGT12, numbers of eggs laid, oviposition period, juvenile hormone III titers, and fat body, and ovarian protein contents. dsUGT12 treatment suppressed NlUGT12 expression and reversed JGM-enhanced effects, resulting in under-developed ovaries and reduced expression of juvenile hormone acid methyltransferase and the JH receptor, methoprene tolerant. Application of the JH analog, methoprene, on dsUGT12 treated-females partially reversed the dsUTG12 influence on vitellogenin synthesis and on NlUGT12 expression. These results represent an important support for our hypothesis.